Cranial electro-stimulation for the amelioration of drug withdrawal symptoms among recovering addicts - Shahab, Syed Alwi (2010)
The problem of drug addiction is receiving urgent attention. Foremost among the treatment problems among drug addicts is the need to help them through the psychologically and physiologically demanding period of withdrawal. The body reacts during this state with a rebound stress response which includes extreme anxiety, depression and insomnia. Underlying the addictive state is an insidious and progressive destruction of normal brain functioning such as severe memory loss, inability to process abstract information, and other organic brain dysfunctions, such as Korsakoff psychosis. Since addiction, withdrawal, and anhedonia are the result of insufficient levels of certain brain chemicals, or undeveloped pleasure centres and pleasure pathways, the most direct way of eliminating them is to restore optimal levels of the brain chemicals, to stimulate the pleasure centres and pleasure pathways. Cranial electro-stimulation is a process which utilizes minute electrical stimulation for therapeutic purposes.